Bottling, Labeling and Selling Honey in Florida - Nancy Gentry; Ellis D James; Mary C Bammer (EDIS)
Honey producers in Florida have two main avenues for selling their hive products. Larger operations must be properly permitted by the Florida Department of Agriculture and Consumer Services and must bottle honey in a certified food establishment. Smaller-scale honey producers, however, may be exempt from needing these licenses, under Florida?s cottage food laws. This 4-page fact sheet written by Nancy Gentry, James D. Ellis, and Mary Bammer and published by the UF/IFAS Entomology and Nematology Department discusses the laws regarding bottling, labeling, and selling honey in Florida both under and outside of the cottage food laws. http://edis.ifas.ufl.edu/in918